Differentiation of Bovine and Porcine Gelatin Based on Spectroscopic and Electrophoretic Analysis - Hermanto, Sandra; Sumarlin, La Ode; Fatimah, Widya (Journal of Food and Pharmaceutical Sciences, 2013)
This study was conducted to explore the differentiation of bovine and porcine gelatins before and after pepsin hydrolysis based on peptide pattern from spectroscopic and electrophoretic analysis due to development of the halal food products analysis. In this study, pepsin (EC 3.4.23.1)Â was used to hydrolyze the two sources of gelatin with consideration to its ability to digest up to 20% of ingested amide bonds by cleaving preferentially after the N-terminal of aromatic amino acids such as phenylalanine, tryptophan, and tyrosine. In this study, we expect to produce the fragment of gelatins with differentiation in relative molecular weights. Gelatins fragments then analyzed by UV-Vis and FTIR spectroscopy to characterize the functional groups on each source of gelatins, followed by SDS-PAGE (Sodium Duodecylsulphate Polyacrylamide Gel Electrophoresis) to identify the molecular weight of the resulting fragments. In UV-Vis spectroscopy, both gelatin source before and after hydrolysis had different absorbance at 229 nm and 240 nm showing the proportion of C=O amida and differences in two-dimensional conformation of the peptide. In terms of FTIR spectra, both gelatin have wavenumber at 3300-3400 cm-1 (NH stretching), 1600 cm-1 (C=O stretching, amida), 1500 cm-1 (C-N stretching), and at 620-767 cm-1 (OCN bending). This indicates that the relative amino acid compositions from two sources of gelatins were relatively different. In contrast, SDS-PAGE analysis does not give a real differentiation, except for porcine gelatin, that fragments which on 2 hour incubation show two peptide fragments with molecular sizes below 36,2 kDa and 28.6 kDa.